Pengaruh Fermentasi Biji Kakao (Theobroma cacao L.) Terhadap Karakteristik Pengeringan - Ansori, Ardy Setya; Waluyo, Sri; Haryanto, Agus; Tamrin, Tamrin (Jurnal Agricultural Biosystem Engineering, 2022)
This research aims to analyze the effect of fermented cocoa beans on drying characteristics.  This research was conducted to examine the drying characteristics of unfermented cocoa beans and fermented cocoa beans.  Fermented cocoa was resulted from two difference levels of yeast as fermentation starter: 3 grams of yeast / 5 kilograms of cocoa and 5 grams of yeast / 5 kilograms of cocoa. As a control, unfermented cocoa beans were also done.  The fermentation chambers were designed with variations in the number of 10, 20 and 30 holes and 12 mm diameters.  The drying cocoa beans were set at a fixed temperature (60 ° C) and drying air velocity of 3.0 km / hour and the power used was 11.34 watts. The results showed that the use of yeast has significant effect on the quality of the dryed cocoa beans using LSD test at  a value of 5%.  Fermented cocoa using 3 grams yeast as starter and 10-holes chamber showed a better drying performances (moisture content and shrinkage).